Superyoung the proven way to stay young forever - Weeks, David (Coronet Books, 1998)
What is it that makes some people look and feel much younger than their true age? This book looks at the 'superyoung' phenomenon. Providing an insight into the factors which halt the ageing process, it also gives you the practical advice to help you to stay young yourself.